Mechanical ventilation as an independent risk factor for mortality in COVID-19-related ARDS: A secondary analysis using propensity score weighting - David Rene Rodriguez Lima; Nicolás Molano-González; Andrea Vargas Villanueva; Dario Isaias Pinilla Rojas; Cristhian Rubio Ramos; Leonardo Andrés Gómez Cortes; Edith Elianna Rodríguez Aparicio; Andrés Felipe Yepes Velasco (PLoS ONE, 2026)
Introduction The optimal role of invasive mechanical ventilation (IMV) in COVID-19–related acute respiratory distress syndrome (C-ARDS) remains uncertain. During the pandemic, many patients with ARDS were managed without IMV, creating a unique opportunity to examine whether IMV is an independent risk factor for mortality rather than a marker of disease severity alone. This study aimed to estimate the adjusted association between IMV and in-hospital mortality in patients with C-ARDS. Methods We performed a secondary analysis of a previously published prospective cohort of adults hospitalized with confirmed C-ARDS at a tertiary center located at high altitude (2,640 m, Bogotá, Colombia). Covariate balancing propensity scores (CBPS) were used to derive inverse probability of treatment weights (IPTW). Weighted logistic regression was then applied to estimate the average treatment effect (ATE) of IMV on in-hospital mortality. As a secondary objective, respiratory mechanics during the first 5 days of IMV were described to evaluate adherence to lung-protective ventilation. Results A total of 1,724 patients with complete data were included; median age was 68 years, 65.9% were male, and overall mortality was 44.8%. Of these, 897 patients (52.0%) required IMV. Mortality differed markedly between groups: 65% in ventilated patients vs. 22% in non-ventilated patients. After IPTW adjustment, IMV remained independently associated with higher mortality (ATE-adjusted OR 7.67; 95% CI 6.20–9.48; p < 0.001). Respiratory mechanics were available for 838 (93.4%) ventilated patients. Median tidal volume, plateau pressure, and driving pressure were initially within protective ventilation targets; however, non-survivors showed small progressive increases in plateau and driving pressures over time. Conclusions In this propensity score–weighted cohort of patients with COVID-19–related ARDS, IMV was strongly associated with in-hospital mortality after adjustment for measured confounders. Ventilatory parameters were generally within protective ranges during the early course of ventilation, although non-survivors showed less favorable longitudinal pressure trajectories. These findings support careful patient selection, optimization of non-invasive support when feasible, and strict adherence to lung-protective ventilation strategies. Residual confounding cannot be excluded.